PENINGKATAN PENDAPATAN DALAM PRODUKSI PALPI MARKISA DI KELURAHAN JAWI-JAWI KABUPATEN BULUKUMBA - -, Fatmawati (Lembaga Penelitian dan Pengabdian pada Masyarakat Universitas Bosowa, 2016)
Geographically location of implementation of production of passion fruit, which is in the village palpi Jawi-Jawi Bulukumbah County, conveniently located under the agriculture with rainwater covering an area of 50.74 hectares and a total production of 187.59 tons/ha. In order to realize the industrialization of the region with raw materials from agriculture as a leading sector through a process of systematic planning, with the real conditions that accommodate the remains exist, it needed a strategic industrial development. The characteristics of the industrial sector of agricultural raw materials and potential local resources to be developed that is in the field of agri-business industry raw material crops horticulture namely passion fruit in abundance and there has been no attention, even though the Government atupun farmers very potential managed to become a product of refined drinks fresh passion fruit. First partner is a group of farmers of passion fruit that perform activities of daily farming horticulture experience problems in processing the cultivation of passion fruit that is post-harvest, and handling of fresh fruit during the harvest so many decomposing because sour taste that is less preferred by consumers to be eaten fresh, solutions on offer is a rare-step post-harvest handling and processing the fruit into products that are preferred by consumers. As for the second partner is a group of housewives and young people who actively melakuakan activities in assisting farmers passionfruit to sell their crops, but experienced problems in selling logs that are cheap, the solution that will be offered are: passion fruit fresh given a touch of appropriate technology to be produced into a drink that is palpi passionfruit.